A Simple Method for the Isolation and Purification of 2,4-Dihydroxy-7-Methoxy-2H-1,4-Benzoxazin-3(4H)-One (DIMBOA) from Maize (Zea mays L.) Seedlings - Jing LI; Xin-gang LIU; Feng-shou DONG; Jun XU; Li-qun GUO; Zhi-qiang KONG; Ying-ying TIAN; Yan-bin WU; Yong-quan ZHENG (Journal of Integrative Agriculture)
2,4-Dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one (DIMBOA), the dominant benzoxazinoid hydroxamic acid in maize (Zea Mays L.), serves as important factors of resistance against insects and microbial diseases, allelochemicals used in competition with other plants. In this paper, a novel and simple method for the isolation and purification of DIMBOA from maize seedlings was developed. Frozen shoots from 7-d-old maize seedlings (1 000×g) were firstly defrosted and then were directly homogenized and extracted with ethyl acetate. The macerate was allowed to stand at room temperature (25±2)°C for 1 h to allow enzymatic release of DIMBOA from DIMBOA-glucoside. Then the ethyl acetate phase was filtered, dried and evaporated to dryness. The resulting light-tan, semicrystalline residue was stored at −20°C for 24 h. Upon recrystallization from acetone-hexane, a relative higher yield (0.58 g) of pure DIMBOA crystals was obtained compared with the yield afforded by Woodward methodology (0.26 g).